No Evidence of Association Between Soccer Heading and Cognitive Performance in Professional Soccer Players: Cross-Sectional Results - Rodrigues, Ana Carolina; Lima, Mariana Drummond Martins; de Souza, Leonardo Cruz; Furtado, Celso; Marques, Cimar Eustáquio; Gonçalves, Lucas; Lima, Marcus Vinícius; Lasmar, Rodrigo Pace; Caramelli, Paulo (Frontiers in Neurology, 2019)
Although the scientific community has focused on the effects of concussions in contact sports, the role of subconcussive impacts, as it can occur during soccer heading, has recently gained attention, considering that it may represent an additional mechanism of cumulative brain injury. The aim of this study is to investigate the effects of soccer heading on cognitive functioning in active professional soccer players. Male soccer players (n=44), from two soccer teams that play in the Brazilian A Series Championship, and non-athletes (n=47), comparable in age and education, were submitted to cognitive assessment, consisting of computerized and conventional neuropsychological testing (Neupsilin battery). In the computerized cognitive assessment, soccer players performed better than controls on reaction time measures in general motor coordination, executive functioning and memory tests, and on accuracy measures in executive functioning tests. There were no significant differences between groups on the Neupsilin battery. A comparison between two sub-groups of soccer players, based on the self-reported number of headings, did not show significant differences on tests performance. No significant correlations were found between an estimate of exposure to heading during professional soccer career and cognitive performance. Our data demonstrate no evidence of cognitive impairment in soccer players, compared to non-athletes, and no association between heading exposure and performance on neuropsychological tests. Longitudinal investigations, including neuroimaging assessment, will help to clarify whether soccer heading may be associated with brain injury and cognitive dysfunction.